With faith in development: Organizing transnational Islamic charity. (July 2017) - Borchgrevink, Kaja; Erdal, Marta Bivand
This article examines the different roles religion can play when migrants organize for development. We focus on organizing for development, through transnational Islamic charity, formally and informally, and where religion takes on explicit or implicit roles. By taking Muslim religious practices as starting points, different forms of development engagements are revealed, than if starting with a focus on so-called 'faith-based organizations' (FBOs). Whereas religion is often seen instrumentally in development studies, we find that the roles of religion are not only functional, but also substantive and relational. The article draws on qualitative data collected in Norway, Pakistan and the UK.